2021
DOI: 10.3389/fcimb.2021.672562
|View full text |Cite
|
Sign up to set email alerts
|

RT-qPCR Assays for Rapid Detection of the N501Y, 69-70del, K417N, and E484K SARS-CoV-2 Mutations: A Screening Strategy to Identify Variants With Clinical Impact

Abstract: BackgroundSeveral variants of the SARS-CoV-2 have been documented globally during the current COVID-19 pandemic. The N501Y, 69-70del, K417N, and E484K SARS-CoV-2 mutations have been documented among the most relevant due to their potential pathogenic biological effects. This study aimed to design, validate, and propose a fast real-time RT-qPCR assay to detect SARS-CoV-2 mutations with possible clinical and epidemiological relevance in the Mexican population.MethodsTargeting spike (S) gene mutations of SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…Recent studies have evaluated different screening kits in comparison to NGS. The authors demonstrated a high concordance between the two methods, reinforcing the interest of screening methods [ 20 , 21 , 22 , 23 , 24 ]. Here, we showed that the PerkinElmer kit performed better than the ID Solution kit, avoiding the problem of mutation detection, notably the detection of E484K mutation.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies have evaluated different screening kits in comparison to NGS. The authors demonstrated a high concordance between the two methods, reinforcing the interest of screening methods [ 20 , 21 , 22 , 23 , 24 ]. Here, we showed that the PerkinElmer kit performed better than the ID Solution kit, avoiding the problem of mutation detection, notably the detection of E484K mutation.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, interactions of NTD deletions with a popular commercial PCR assay (TaqPath SARS-CoV-2 Assay, Thermo Fischer, Waltham, MA, USA) first directed attention to the expanding B.1.1.7 lineage in Great Britain, thereby hinting at the potential utility of specific qPCR tests for variant prediction [28,29]. The recent surge in publications regarding PCR-typing demonstrates the wide spectrum of potential methods and their varying degrees of suitability for practical use in diagnostics [9][10][11][12]14].…”
Section: Discussionmentioning
confidence: 99%
“…Spike gene mutations such as N501Y, E484K/Q, L452R, and P681H/R have occurred independently in multiple VOCs and VOIs (variants of interest), enabling dynamic adaptation of existing assay designs to detect emerging SARS-CoV-2 variants [7]. RT-qPCR is the gold standard for detection of SARS-CoV-2 in clinical samples [8] and has also been used for SARS-CoV-2 spike gene mutation detection in previous studies, often focusing on the HV69/70 deletion and the N501Y SNP (single nucleotide polymorphism) using various methods such as specific primers, simple probes, and melt curve analyses [9][10][11][12][13][14][15]. Locked nucleic acid (LNA)-Probes represent a well described method for specifically detecting SNPs by RT-PCR [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Such an assay can help assess a variant's frequency within a population and contribute to policy guidelines. Indeed a number of publications targeting variants of concern detection using RT-qPCR ( Barreto et al, 2020 ; Bivins et al, 2021 ; Gand et al, 2021 ; Vega-Magaña et al, 2021 ; Vogels et al, 2021 ; H. Wang et al, 2021 ; Yaniv et al, 2021 ) as well as available commercial kits (e.g., TaqPath ThermoScientific, GT molecular, PerkinElmer) have emerged for individual assessments.…”
Section: Introductionmentioning
confidence: 99%